Evaluation of the Effects of Sildenafil Citrate (Viagra) on Vertebral Artery Blood Flow in Patients with Vertebro-Basilar Insufficiency - Bozgeyik, Zulkif; Berilgen, Sait; Ozdemir, Huseyin; Tekatas, Aslan; Ogur, Erkin (Korean Radiological Soc, 2008)
Objective: To investigate the effects of sildenafil citrate (Viagra) on the vertebral artery blood flow of patients with vertebro-basilar insufficiency (VBI) using color duplex sonography (CDS). Materials and Methods: The study included 21 patients with VBI (aged 31-76; mean 61.0 +/- 10.5 yrs). We administered a 50 mg oral dose of sildenafil citrate to all patients. Next, we measured the peak systolic velocity (Vmax), end diastolic velocity (Vmin), resistive index (RI), pulsatility index (PI), diameter, area, and flow volume (FV) of vertebral arteries using CDS before the administration of sildenafil citrate; 45 minutes after, and 75 minutes after administration. Statistical testing was performed using SPSS for windows version 11.0. The statistical test used to determine the outcome of the analysis was the repeated measures analysis of variance (ANOVA) test. Results: Compared to the baseline values, the vertebral artery diameter, area, and FV increased significantly following the administration of sildenafil citrate. The diameter, area and FV increased from 3.39 mm at 45 minutes to 3.64 mm at 75 minutes, 9.43 cm(2) to 10.80 cm(2) at 45 minutes and 10.81 cm(2) at 75 minutes, as well as from 0.07 L/min at baseline to 0.09 L/min at 45 minutes and unchanged at 75 minutes, respectively. Conclusion: Sildenafil citrate elicited a significant effect on vertebral artery diameter, area and FVs.
Keywords: Sildenafil citrate; Vertebral artery; Color duplex sonography; Vertebro-basilar insufficiency